NEUROBIOLOGICAL PREDICTORS OF RESPONSE TO DORSOLATERAL PREFRONTAL CORTEX REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION IN DEPRESSION: A SYSTEMATIC REVIEW. Issue 12 (18th September 2015) - Silverstein, William K.; Noda, Yoshihiro; Barr, Mera S.; Vila‐Rodriguez, Fidel; Rajji, Tarek K.; Fitzgerald, Paul B.; Downar, Jonathan; Mulsant, Benoit H.; Vigod, Simone; Daskalakis, Zafiris J.; Blumberger, Daniel M.
Abstract : Background: A significant proportion of patients with depression fail to respond to psychotherapy and standard pharmacotherapy, leading to treatment‐resistant depression (TRD). Due to the significant prevalence of TRD, alternative therapies for depression have emerged as viable treatments in the armamentarium for this disorder. Repetitive transcranial magnetic stimulation (rTMS) is now being offered in clinical practice in broader numbers. Many studies have investigated various different neurobiological predictors of response of rTMS. However, a synthesis of this literature and an understanding of what biological targets predict response is lacking. This review aims to systematically synthesize the literature on the neurobiological predictors of rTMS in patients with depression. Methods: Medline (1996–2014), Embase (1980‐2014), and PsycINFO (1806‐2014) were searched under set terms. Two authors reviewed each article and came to consensus on the inclusion and exclusion criteria. All eligible studies were reviewed, duplicates were removed, and data were extracted individually. Results: The search identified 1, 673 articles, 41 of which met both inclusion and exclusion criteria. Various biological factors at baseline appear to predict response to rTMS, including levels of certain molecular factors, blood flow in brain regions implicated in depression, electrophysiological findings, and specific genetic polymorphisms. Conclusions: Significant methodological variability in rTMS treatment protocols limits the ability to generalize conclusions. However, response to treatment may be predicted by baseline frontal lobe blood flow, and presence of polymorphisms of the 5‐hydroxytryptamine (5‐HT) ‐1a gene, the LL genotype of the serotonin transporter linked polymorphic region (5‐HTTLPR) gene, and Val/Val homozygotes of the brain‐derived neurotrophic factor (BDNF) gene.